Chemistry in context : applying chemistry to society - Fahlman, Bradley D.; Purvis-Roberts, Kathleen; Kirk, John S.; Kelly, Resa M.; Daubenmire, Patrick L.; American Chemical Society (New York, NY : McGraw-Hill Education, 2021)
"Climate change. Water contamination. Air pollution. Food shortages. These and other global issues are regularly featured in the media. However, did you know that chemistry plays a crucial role in addressing these challenges? A knowledge of chemistry is also essential to improve the quality of our lives. For instance, faster electronic devices, stronger plastics, and more effective medicines and vaccines all rely on the innovations of chemists throughout the world. With our world so dependent on chemistry, it is unfortunate that most chemistry textbooks do not provide significant details regarding real-world applications. Enter Chemistry in Context-"the book that broke the mold." Since its inception in 1993, Chemistry in Context has focused on the presentation of chemistry fundamentals within a contextual framework"--
"A project of the American Chemistry Society."
Includes index.
Ages 18+
Grades 10-12
Keywords: Biochemistry; Environmental chemistry; Geochemistry